Financial Data Processing Application On Optical Annisa Blitar - Sendi Dwi Jayanti; Sri Lestanti; Ni'ma Kholila (Universitas Muhammadiyah Sidoarjo, 2021)
Information technology is growing faster, now with the presence of information technology, companies can do business more easily, one of which is the business of optics. Optik Annisa Jaya is one of the companies engaged in the field of glasses in the city of Blitar. Optik Annisa still has several shortcomings, one of which is a mechanism where obstacles in managing financial report data are still carried out by manual processing from recording sales transaction notes and recorded in sales transaction records so that it takes a long time. For making this application using the system development method, namely the method waterfall, a desktop-based application that uses php desktop as the interface design and SQLite as the database. The application testing process uses black box testing using the ISO 9126 standard. Based on the table of results of the assessment of Financial Data Processing Applications at Optik Annisa by media experts, media experts obtained an average feasibility percentage score of (89.5%) in the